Perancangan Antena Mics Implanted Untuk Monitoring Detak Jantung Berbasis HFSS 13.0. - Muhammad Yaser; Untung Priyanto (Website, 2019)
The medical implantable communications system (MICS) is one of the emerging technologies in the health sector where the implant device, in this case the antenna, is inserted into the human body between the skin layer and the fat. One application is for monitoring patient conditions such as heart rate and blood pressure. Microstrip antennas in the MICS application work in 402-406 MHz frequency range. In this paper, design and simulation of implant antenna is presented. The implant antenna is simulated using High Frequency Simulator Software (HFSS) using miniaturization, biocompatibility and biomaterial techniques. The antenna will be implanted in the upper arm model. The antenna specifications are as follows: the physical size of the antenna is 32 ´ 40 ´ 4 mm with a working frequency of 403.03 MHz which corresponds to the MICS frequency standard of 402-405 MHz. The VSWR simulation result is 1.2, which has met the standard VSWR value ≤ 2 on the rectangular antenna, which is generally considered as good. The gain is -27 dBi, which is considered good according to the standard (-31.5 dBi) and the SAR is 12.7 W/kg per 1g.Medical implantable communications system (MICS) adalah salah satu teknologi yang sedang berkembang dalam bidang kesehatan. Dengan teknologi ini perangkat implan, dalam hal ini antena, dimasukkan ke dalam tubuh manusia di antara lapisan kulit dan lemak. Salah satu aplikasinya yaitu untuk memonitor kondisi pasien seperti detak jantung dan tekanan darah. Antena mikrostrip pada aplikasi MICS bekerja pada rentang frekuensi 402-406 MHz. Antena implan yang dirancang disimulasikan dengan menggunakan High Frequency Simulator Software (HFSS) dengan menggunakan teknik miniaturisasi, biocompatibilitas, dan biomaterial. Antena akan ditanamkan pada model lengan bagian atas. Dari hasil simulasi didapat spesifikasi antena sebagai berikut: ukuran fisik antena sebesar 32 ´ 40 ´ 4 mm dengan frekuensi kerja 403,03 MHz yang sesuai dengan standard frekuensi MICS sebesar 402-405 Mhz. Hasil simulasi VSWR sebesar 1,2 sudah memenuhi standar nilai VSWR ≤ 2 yang dianggap baik pada antena rectangular. Gain sebesar -27 dBi, yang telah memenuhi standar sebesar -31,5 dBi dan SAR sebesar 12,7 W/kg per 1g.